How do you solve the system x+3y=-4 and 2x+6y=5 using substitution?

1 Answer
Oct 16, 2016

This systen has no solutions. See explanation for details.

Explanation:

The original system is:

{(x+3y=-4),(2x+6y=5):}

To solve it using substitution we have to calculate one of the variables from one equation to substitute it in the other. We can easily calculate x from the first equation:

x=-4-3y

Now we put the value to the second equation:

2(-4-3y)+6y=5

If we try to calculate y from this equation we get:

-8-6y+6y=5

If we reduce like terms we get:

-8=5

This equality is of course false which means that the original system has no solutions.